Princely Patronage and Patriot Cause: Corruption and Public Value Dynamics in the Dutch Republic (1770s–1780s). (2nd January 2016) - Kerkhoff, Toon
Abstract : While the usefulness of historical insight is often implicitly recognized in public values studies, it is rarely expressed in actual historical research. This article argues that historical analysis is well equipped to investigate public values and their dynamics (i.e., change and continuity over time). To illustrate this argument, the article presents a corruption scandal involving the regent Hugo Repelaer in the Dutch Republic of the 1770s and 1780s. The article shows how patronage and other forms of political behavior were contested on the basis of new and/or reemphasized public values and political principles, such as popular sovereignty and representation. It also shows the emergence of value monism in the Dutch context. An explicit link between the events of the case and theoretical perspectives on public value dynamics serves, furthermore, to increase the understanding of the latter and to elucidate present discussions. The article contends that a historical approach to public values can and should inform present-day attitudes to corruption and integrity, and offers promising avenues for future historical research on public values on a European scale.